Feminism and New Men's Support for Gender Equality - Islam, Amaliyah Izzul; Kuswanti, Ana; Tayinapis, Radita Gora; Muqsith, Munadhil Abdul (Riwayat: Educational Journal of History and Humanities, 2025)
This research examines the concept of "new men" in the context of feminism and their involvement in supporting gender equality. Although the feminist movement has shown significant progress, men's involvement is still limited due to toxic masculinity and deep-rooted patriarchal norms. This research aims to investigate the new role of men in deconstructing traditional gender roles, especially in domestic and childcare tasks that women often bear. Gender equality theory and international regulations such as CEDAW, the Beijing Declaration, and related national regulations form the basis of analysis. Using qualitative descriptive methods, this research analyzes global survey data which shows increasing awareness of the role of men, but is faced with cultural challenges that maintain traditional views. The research results show that men are starting to advocate for gender equality. However, they still face various challenges, ranging from social stigma, and loss of social status, to a deep-rooted patriarchal culture. This research argues that there is a need for new men, namely men who dare to go against the current and social stigma to break patriarchal culture. These new men do things that previously patriarchal men rarely did, namely, become stay-at-home dads, cooking, or caring for children. Men's involvement in gender equality campaigns is important because it can improve the quality of life, change social norms, and create constructive dialogue. In conclusion, men's involvement is justification that there is something wrong with the patriarchal norms that society has adhered to